BODY MASS INDEX AND ALBUMIN LEVELS ARE ASSOCIATED WITH PULMONARY FUNCTION PARAMETERS IN PEDIATRIC SUBJECTS WITH CYSTIC FIBROSIS - Miriam Isabel Souza dos Santos Simon; Gabriele Carra Forte Paulo; José Cauduro Marostica (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To evaluate the association of body mass index (BMI) and albumin with pulmonary function in cystic fibrosis (CF) pediatric subjects. Methods: This is a cross-sectional study with clinically stable CF's subjects. Clinical (pulmonary function) and nutritional evaluation (body mass index and albumin) were performed. Univariate analysis was performed using simple linear correlations. Regression analysis was performed using an exit level of p<0.05. Results: Seventy-eight CF's subjects (mean age 12.8±3.8 years) with mean albumin 4.2±0.4 mg/dL, predicted forced expiratory volume in 1 second (FEV1%) 80.8±22.6 and BMI median percentile 51.2 (1.3-97.7). In the multiple regression models, albumin, age and BMI percentile were associated with pulmonary function. Subjects with lower than 25 BMI percentile had 12.2% lower FEV1%. An albumin increase of 0.1 mg was associated with 2.7% increase in predicted FEV1%, and one year increase in age was associated with reduction in 1.2% of predicted FEV1%. Conclusions: BMI percentile, albumin and age were independently associated with predicted FEV1% in a tertiary referral hospital.